Flexible energy harvester from an organic ferroelectric ammonium salt - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zareba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry-An Asian Journal, 2021)
Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two-component ammonium salt 2, containing a bulky [Bn(4-BrBn)NMe2](+) (Bn=benzyl and 4-BrBn=4-bromobenzyl) cation and tetrahedral (BF4)(-) anion. The structural analysis revealed the presence of rich non-classical C-H...F and C-H...Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization (P) vs. electric field (E) hysteresis loop measurements on 2 gave a remnant polarization (P-r) of 14.4 mu C cm(-2) at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak-to-peak output voltage of 20 V, maximum current density of 1.1 mu A cm(-2) and power density of 21.1 mu W cm(-2) were recorded for the 15 wt% 2-TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 mu F capacitor, with stored energies and measured charges of 156 mu J and 121.6 mu C, respectively.
Keywords: Dielectric; energy harvesting; ferroelectricity; organic composites; piezoelectric

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus

Enhancing the crystallization kinetics and mechanical properties of poly(lactic acid) blends for 3D printing application - Kothavade, Premkumar; Yadav, Prashant; Gopal, Animesh; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2024)
3D printing of poly(lactic acid) (PLA) blends has been attempted to resolve issues such as inherent brittleness and slow crystallization rate of PLA. However, a persistent challenge remains in the form of phase separation or gradual migration of the blended soft polymer or plasticizers. To simultaneously enhance the miscibility of the blends and toughness of 3D-printed parts, a triblock copolymer PLA-PEG-PLA was synthesized and blended with PLA in varying proportions (5, 10, 15, and 20 wt %). Blending only 10-20 wt % low molecular weight PLA-PEG-PLA into PLA yielded a miscible blend that showed a 45-fold increase in elongation at break and a 23-fold enhancement in toughness over neat PLA. Scanning electron microscopy (SEM) images of fractured cross sections revealed a brittle to ductile transition in 3D-printed PLA/PLA-PEG-PLA samples. Isothermal crystallization studies and data analysis using the Avrami equation showed an enhancement in the crystal growth rate and overall rate of crystallization. The blends achieved half of their crystallinity in approximately 3 min, a significant improvement over the 9 min required by PLA alone. This underscores the efficiency of our approach. This was also evident in the spherulite growth of 3D-printed PLA and mPLA blends when examined using polarized optical microscopy (POM). To the best of our knowledge, this is the first report exploring the use of blends that include PLA and low molecular weight PLA-PEG-PLA triblock copolymers for 3D printing applications.
Keywords: Crystallization; FFF 3D printing; PLA-PEG-PLA triblock copolymer; poly(lacticacid); toughness

Extrusion 3D printing of intrinsically fluorescent thermoplastic polyimide: revealing an undisclosed potential - Kothavade, Premkumar; Kafi, Abdullah; Dekiwadia, Chaitali; Kumar, Viksit; Sukumaran, Santhosh Babu; Shanmuganathan, Kadhiravan; Bateman, Stuart (POLYMERS, 2024)
Keywords: Additive manufacturing; functional extrusion; high-performance polymers; thermoplastic polyimide

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity